KEMAMPUAN DUA SPESIES Enterobacter sp. SEBAGAI BAKTERI PEMACU PERTUMBUHAN TANAMAN KENTANG (Solanum tuberosum L.) PADA KONDISI CEKAMAN KEKERINGAN - Khoirun Enisa Maharina; Nurul Aini; Luqman Qurata Aini (Universitas Tribhuwana Tunggadewi, 2017)
Enterobacter xiangfangensis and Enterobacter cloaceae are known to have the ability as a phosfat solubilizing and producing hormone IAA. Their also have ability to survive under drought stress in vitro assay conditions. Both of these bacteria has good potential as a potato plant growth promoting bacteria, especially in drought stress conditions. This is an alternative to improve tolerance and growth of the potato crop in drought stress conditions. The results showed that the level of drought stress 75% of field capacity can boost the potential of endophytic bacteria E. xiangfangensis in increasing leaf area, plant dry weight, root length and physiological activity i.e total phosphorus content in potato plants. Endophytic bacteria E. xiangfangensis is better to increase potato plant height than endophytic bacteria E. cloaceae. These results are supported by the results of potential test of E. xiangfangensis which have the advantage of producing hormones IAA compared with E. cloaceae. Furthermore, in drought stress conditions 50% of field capacity and 75% of field capacity have different effects on the observations of root length growth parameters potato plants.